El uso del GIS como estrategia didáctica en el estudio del bloque 4: Los continentes, en octavo año de EGB. - Tigse León, Franklin Joel (2025)
The integration of digital tools in the educational field has become a key aspect in responding to the demands of 21st-century learning. In this context, Geographical Information Systems (GIS), known in Spanish as Sistemas de Información Geográfica, stand out as innovative didactic resources that strengthen the teaching of geographic content through the representation, analysis, and interpretation of spatial data. Therefore, the purpose of this research was to examine the use of GIS as a pedagogical tool in addressing Block 4: The Continents, corresponding to the eighth year of Basic General Education (EGB). The study employed a bibliographic, descriptive, and technological approach. Based on a theoretical and methodological review, an educational proposal was created by the official planning format of the Ministry of Education of Ecuador, which illustrates the use of software such as Atlas.com, QGIS, and Google Earth Pro, among others, to support the optimization of the teaching-learning process. This proposal aims to serve as a practical guide for teachers to integrate GIS into their classes, promoting more meaningful learning aligned with the challenges of contemporary education. In conclusion, incorporating GIS in the classroom represents an opportunity to transform traditional teaching and make it more dynamic. Teachers need to receive continuous training and adapt strategies to the school environment.